Improving CO2 mass transfer in microalgal cultures using an oscillatory flow reactor with smooth periodic constrictions. Issue 6 (December 2021) - Gonçalves, Ana L.; Almeida, Filipe; Rocha, Fernando A.; Ferreira, António
Abstract: Although very promising, the use of microalgae for CO2 capture still faces some limitations. Due to the low solubility of this gas in the liquid medium, poor CO2 utilisation efficiencies by microalgae are very common, resulting in low CO2 fixation rates and CO2 losses to the atmosphere. Considering this limitation, several researchers have focused on improving photobioreactor (PBR) design to increase CO2 gas-liquid mass transfer rates. However, these systems typically rely on high fluid turbulence and power consumption due to CO2 gas compression. As an alternative, this study proposes using an oscillatory flow reactor with smooth periodic constrictions (OFR-SPC). So far, this reactor design has been successfully applied to improve the mixing efficiency of several chemical processes. However, there is no evidence of its use for microalgal cultivation. To evaluate its potential for microalgal biomass production, a detailed characterisation of CO2 mass transfer was performed. CO2 mass transfer and bubbles' dynamics were evaluated under different operational conditions: (i) oscillation amplitude and frequency; (ii) aeration rate; (iii) CO2 concentration in the inlet gas; and (iv) biomass concentration. This study made it possible to understand the effect of each process variable on the individual values of liquid-side mass transfer coefficient, k L, and specific interfacial area, a . According to the results, CO2 gas-liquid mass transfer was enhanced by increasing the oscillatory movement, aeration rate and CO2 concentration. Moreover, this study demonstrated that promising CO2 mass transfer rates can be achieved without significantly increasing power consumption and fluid turbulence. Graphical Abstract: ga1 Highlights: CO2 gas-liquid mass transfer in microalgal cultures was evaluated in an OFR-SPC. An increase in the oscillatory and aeration conditions improves CO2 mass transfer. Higher CO2 concentrations in the inlet gas further improve CO2 mass transfer. Higher biomass concentrations have slightly improved CO2 mass transfer. The OFR-SPC provides CO2 mass transfer rates comparable to conventional PBRs.